The Isosteroid Alkaloid Imperialine from Bulbs of Fritillaria cirrhosa Mitigates Pulmonary Functional and Structural Impairment and Suppresses Inflammatory Response in a COPD-Like Rat Model - Dongdong Wang; Qingdan Du; Houcong Li; Shu Wang (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the world. Present therapies for COPD have limited effect on reducing the progression of COPD and suppressing the inflammatory response in the lung. Bulbs of Fritillaria cirrhosa D. Don (BFC) have been used in many Asian countries for a long time to treat pulmonary diseases, such as cough, expectoration, and asthma. Steroidal alkaloids are the major biological active constituents in BFC, whereby imperialine is one of the important steroidal alkaloids. So far, there are no studies reporting the effect of imperialine on COPD. In this study, we investigated the effect of imperialine on pulmonary function and structure and inflammation in a COPD-like rat model which was induced by the combination of exposure to CS and intratracheal administration of LPS. Our data show that imperialine mitigates pulmonary functional and structural impairment and suppressed inflammatory response in a COPD-like rat model by mediating expression of related cytokines in lung tissues of the COPD-like rats, such as IL-1β, IL-6, IL-8, TNF-α, NF-κB, TGF-β1, MMP-9, and TIMP-1.